SUNTIANG MANGKUTO DI KANAGARIAN SUNGAYANG KABUPATEN TANAH DATAR - Gustina, Gustina; Efi, Agusti; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2017)
The purpose of research is describe the form of suntiang mangkuto and analyze the inner meaning of suntiang mangkuto . This research is a descriptive kualitatif. Object this research is suntiang mangkuto. Data collection techniques with observation, interview and documentation. Analysis techniques with reduction data, display of data and conclusion. The results of resesearch obtained form suntiang mangkuto resembles a crown shape with a diameter of 17,1 cm has 4 support bars with a width of 2 cm has wide range of decorative flora and fauna materials used for the manufacture of suntiang mangkuto the original and the latest. The meaning of philosophy contained in suntiang mangkuto is that women in minangkabau should not uphold the heavy burden. Suntiang mangkuto show beauty and serves as a golden yellow colored flowers on suntiang mangkuto symbolizes custom rules and customary philosophy in minangkabau that is nature takambang be a teacher.2Keywords : Suntiang Mangkuto, clothes, Minangkabau